The investment-intervention approach for welfare states - Erola, Jani; Moisio, Pasi; Peltoniemi, Johanna (Edward Elgar Publishing, 2026)
The social investment paradigm has dominated European policy thinking and reforms for more than two decades, but it has been criticised for neglecting acute risks and reproducing inequalities. This chapter introduces the social investment-intervention (SI+I) approach as a complementary framework that addresses these limitations. The SI+I approach unites proactive prevention of negative outcomes through long-term investments with the immediate rectification of current problems using targeted interventions. It is resilient in the face of shocks, inclusive in reaching vulnerable populations, and adaptive in employing empirical evidence to adjust or even replace ineffective policies. In developing and implementing new policies, the SI+I approach prioritises effectiveness and affordability, focuses on changing outcomes rather than causes, and embeds positive goals in services and transfers. By integrating perspectives from social sciences, health sciences, and educational research, the SI+I approach also provides a shared framework for linking diverse disciplinary insights to welfare state reform, while also bridging model-based and design-based traditions in assessing effectiveness.
Beyond the Nordic Welfare State : Extending Social Investments with Interventions